(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Ventricular septal defect (VSD) is a deficiency of the septum separating the ventricles. Usually, ventricular septal defects are correctly diagnosed when their dimensions exceed 4 mm, however, diagnosis of smaller defects is also possible. Various congenital heart defects were reported in 182 fetuses/newborns, among which breast cancer accounted for 25.8% (+3.2) or 47 cases. The age of the patients in the study group ranged from 18 to 40 years old. Early prenatal diagnosis was possible in 11 (23.4%+6.2) fetuses between 11 weeks of one day and 13 weeks of six days of pregnancy and was performed according to generally accepted diagnostic criteria. In the second half of pregnancy, DMF was additionally diagnosed in 7 (14.9%+5.2) fetuses. In the group with undiagnosed prenatal congenital heart defects, breast cancer was registered in 29 (61.7%+7.1) newborns. Various echographic markers and their combination were registered in 10 out of 11 (90.9%+8.7) fetuses with breast cancer diagnosed in early pregnancy. A thorough study of the ultrasound anatomy of the fetus made it possible to detect various extracardial abnormalities in 6 out of 11 (54.5%+15.0) fetuses at an early date. The outcome of pregnancy in the study group of fetuses was more often marked as favorable. Pregnancy ended with urgent delivery and the birth of live children in 37 (78.8%+6.0) patients.